The concept and conceptions of transnational and global law - Matej Avbelj (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
The following contains a transcript of the workshop, which was held in June 2015 at the Graduate School of Government and European Studies in Ljubljana, Slovenia. The workshop marked the final stage of Dr. Avbelj's research project, supported by the Slovenian Research Agency, which was dedicated to the Post-modern challenges of transnational law to the European Union. The workshop gathered four leading scholars in the field of transnational and global legal studies: Jose-Manuel Barreto, Mattias Kumm, Gianluigi Palombella and Neil Walker. They have touched on the contemporary most pressing issues of transnational and global legal regulation.
Keywords: 320; transnational and global legal regulation